Hubungan Asupan Zat Besi, Kadar Hemoglobin, dan Status Gizi terhadap Kebugaran Jasmani Remaja Putri di MA Al-Irsyad Gajah: Correlation between Iron Consumption, Hemoglobin Level, and Nutritional Status on the Physical Fitness of Young Women at MA Al-Irsyad Gajah - Hardiansyah, Angga; Khasanah, Arini Noor; Hayati, Nur (Universitas Airlangga, 2024)
Background: Good nutritional status, normal hemoglobin levels, and adequate iron consumption will help a person achieve good physical fitness. Lack of iron consumption causes a decrease in hemoglobin production. Low levels of hemoglobin cause disruption of oxygen transport to whole body associated with energy production. Malnutrition or excess nutritional status causes a person to have difficulty moving, which results in a lower level of physical fitness. Objectives: To determine the relationship between iron consumption, hemoglobin level and nutritional status on the physical fitness of female adolescents. Methods: The study used a cross-sectional design, with total sample of 65 respondents. The data were nutritional status from BMI/U, hemoglobin levels using the Easytouch GCHb (Glucose, Cholesterol, and Hemoglobin) tool, iron consumption using food recall, and physical fitness measured using beep test. Bivariate analysis was measured by Gamma correlation test and ordinal logistic regression test for multivariate analysis. Results: Most of respondents had good nutritional status (55.4%), normal hemoglobin levels (69.2%), good iron consumption (58.5%), and sufficient physical fitness (60%). The results of bivariate analysis showed that nutritional status did not correlate with physical fitness (p=0.905). Meanwhile, hemoglobin level and iron consumption correlated with physical fitness (p=0.004). Multivariate analysis explained that hemoglobin levels had a 1.73 effect on physical fitness compared to iron intake which influenced physical fitness by 1.1 times. Conclusions: There is a correlation between iron consumption and hemoglobin levels with physical fitness. There is no correlation between nutritional status and physical fitness.